Fractured clasts in the Mt Currie Conglomerate at Kata Tjuta (Central Australia): evidence of Early Cambrian earthquakes? - Tokarski, Antek K.; Strzelecki, Piotr J. (Geology, Geophysics and Environment, 2020)
Lower Cambrian Mt Currie conglomerate at Kata Tjuta bornhardts (Central Australia) bears numerous fractured clasts. Clast-cutting fractures are restricted to particular clasts, the matrix of the conglomerate is not fractured. The fractures are tectonic joints of two sets. The joints were formed due to either seismic or aseismic deformation. In the former case, the fractures may result from Early Paleozoic earthquakes.